Задатчик інтенсивності для пристрою плавного пуску електродвигуна заглибного насоса - Лобов, В.Й.; Лобова, К.В. (Електротехніка і електромеханіка, 2016)
Розглядається задача побудови задатчика інтенсивності для формування зміни кута відкривання тиристорів регулятора напруги. Це дозволяє змінювати по складній траєкторії напругу живлення на статорі електродвигуна заглибного насосу, забезпечуючи цим потрібний час плавного прискорення обертання ротора. Для реалізації задатчика інтенсивності апаратними засобами автоматизації надано блок-схему, а програмним шляхом – математичні вирази. Рассматривается задача построения задатчика интенсивности для формирования изменения угла открывания тиристоров регулятора напряжения. Это позволяет менять по сложной траектории напряжение питания на статоре электродвигателя погружного насоса, обеспечивая, тем самым, нужное время плавного ускорения вращения ротора. Для реализации задатчика интенсивности аппаратными средствами автоматизации представлена блок-схема, а программным путем – математические выражения Purpose. Development of an intensity setter, which in a rational law changes the opening thyristor the voltage regulator and effectively to changing power supply voltage stator windings of the electric pump deepening, ensuring a smooth start in a wide range. Methodology. Electric submersible pump belongs to the small inertia electric, since it is not significant total moment of inertia, not exceeding two moments of inertia of the motor and static moment on the shaft does not exceed forty percent of the nominal torque. For technical requirements that electric acceleration time should have no less than twenty seconds or more. Office starting modes of electric submersible pumps economically justified using thyristor voltage regulator by forming the dial changes the intensity of the necessary legislation in time voltage feeding the stator windings. This ensures a smooth start right rotor of the electric submersible pump. Results. A block diagram of the intensity setter that is: with control unit, two units that form the exponential voltage supply emitter follower and regulatory elements. The mathematical expressions for voltage at the stator windings of the motor, changing exponentially, opening the angle of thyristor power unit thyristor the voltage regulator, which is determined through the initial angle of opening. Provided formula for pick-up voltage and minimum voltage, time constants, which are determined from the basic equations of motion and mechanical characteristics of the electric motor. Analytical investigated by the voltage dependence violation by changing the time constant flowing and growing exhibitor supply voltage stator electric circuit deepening pump. Originality. Proposed in the initial time on the stator windings of the electric pick-up voltage is applied. Under the influence of this voltage, motor rotor begins to accelerate. At the same time, pickup voltage decreases the minimum startup voltage varies exponentially in which the rotor of the electric motor continues to rotate more steadily. Now the voltage at the motor stator windings increases exponentially to the nominal voltage of the supply network. This start flowing smoothly for the right time to establish nominal rotor speed of the motor. Practical value. Developed dial allows you to increase the intensity of the electric motor acceleration time and reduce the dynamic loads of the electric submersible pump.